Moderate Dietary Protein Restriction Optimized Gut Microbiota and Mucosal Barrier in Growing Pig Model - Chen, Xiyue; Song, Peixia; Fan, Peixin; He, Ting; Jacobs, Devin; Levesque, Crystal L.; Johnston, Lee J.; Ji, Linbao; Ma, Ning; Chen, Yiqiang; Zhang, Jie; Zhao, Jinshan; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Appropriate protein concentrations are essential for animals at certain stage. This study evaluated the effects of different percentages of dietary protein restriction on intestinal health of growing pigs. 18 barrows were randomly assigned to a normal (18%), low (15%) and extremely low (12%) dietary protein concentration group for 30 days. Intestinal morphology and permeability, bacterial communities, expressions and distributions of intestinal tight junction proteins, expressions of biomarkers of intestinal stem cells (ISCs) and chymous bacterial metabolites in ileum and colon were detected. The richness and diversity of bacterial community analysis with Chao and Shannon index were highest in the ileum of 15% CP group. Ileal abundance of Streptococcaceae and Enterobacteriaceae decreased while beneficial Lactobacillaceae, Clostridiaceaeˍ1, Actinomycetaceae and Micrococcaceae increased with a protein reduction of 3 percentage points. Colonic abundance of Ruminococcaceae, Christensenellaceae, Clostridiaceaeˍ1, Spirochaetaceae and Bacterodales_S24-7_group declined, while Lachnospiraceae, Prevotellaceae and Veillonellaceae increased with dietary protein reduction. Concentration of most bacterial metabolites decreased with decreasing dietary protein concentration. Ileal barrier function reflected by tight junction proteins (occludin, zo-3, claudin-3 and claudin-7) did not show significant decrease in 15% CP group while sharply reduced in the 12% CP group compared to 18 % CP group. And in 15% CP group, the ileal distribution of claudin-3 mainly located at the cell membrane with complete morphological structure. In low-protein treatments, development of intestinal villi and crypt was insufficient. The intestinal permeability reflected by serous lipopolysaccharide (LPS) kept stable in the 15% CP group while increased significantly in the 12% CP group. The expression of ISCs marked by Lgr5 slightly increased in ileum of the 15% CP group. Colonic expression of tight junction proteins declined in extremely low protein levels. In conclusion, moderate protein restriction (15% CP) can optimize the ileal microbiota structure via strengthening beneficial microbial populations and suppressing harmful bacterial growth and altering the function of ileal tight junction protein as well as epithelial cell proliferation.